A constructive critique of religion encounters between Christianity, Islam and non-religion in secular societies - Lövheim, Mia 1968-; Stenmark, Mikael 1962- (Bloomsbury Academic, 2020)
"Increasing religious diversity and the associated confrontations between those with different worldviews means there is a pressing need to engage with how constructive interaction and critique can be developed across diverse interests. Contributors to this collection tackle this challenge through an analysis of the reasons underpinning a critique of religion in institutional contexts of secular democratic societies. They explore how social and cultural conditions shaping these institutions enable and structure a critical and constructive engagement across diverging worldviews. This dual approach offers an innovative way of addressing the question of why some strategies for critique of religion seem to be more beneficial for constructive engagement, whereas others increase intolerance, polarization, and conflict. A key argument running through the book is that to develop constructive forms of critique a more thorough and systematic investigation of resources for criticism located within religious worldviews themselves is needed. This investigation needs to be anchored in an analysis of conditions under which such resources can be accommodated within particular social institutions. Chapters address how critique of Islam and Christianity in particular is expressed in academia, the law, politics, media, civil society, education and parenting with a focus on Northern Europe and North America. The interdisciplinary approach, which combines theoretical perspectives from theology, philosophy, religious studies, history, sociology, law, and educational studies with empirical case studies, contributes to advancing studies of the complex and contentious character of religion in contemporary society"--